1995
DOI: 10.1007/bf01921741
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix of the hematopoietic microenvironment

Abstract: The bone marrow microenvironment plays an important role in promoting hematopoietic progenitor cell proliferation and differentiation and the controlled egress of these developing hematopoietic cells. The establishment of long-term bone marrow cultures, which are thought to mimic hematopoiesis in vitro, and various stromal cell lines has greatly facilitated the analysis of the functions of this microenvironment. Extracellular matrix (ECM) molecules of all three categories (collagens, proteoglycans and glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
110
0
16

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 106 publications
1
110
0
16
Order By: Relevance
“…Cytokine-related stimulation allows the overexpression of this receptor. The abnormalities found in ECM components could alter the co-localization of the diverse growth factors and cytokines, which are required to modulate the growth and differentiation process of hematopoietic cells (12,28,35). This in turn may alter the cell-cell and cell-ECM interactions, thereby modifying the signaling pathways and leading to bone marrow hypoplasia with a depletion of progenitor hematopoietic populations and peripheral pancytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-related stimulation allows the overexpression of this receptor. The abnormalities found in ECM components could alter the co-localization of the diverse growth factors and cytokines, which are required to modulate the growth and differentiation process of hematopoietic cells (12,28,35). This in turn may alter the cell-cell and cell-ECM interactions, thereby modifying the signaling pathways and leading to bone marrow hypoplasia with a depletion of progenitor hematopoietic populations and peripheral pancytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…3), known to control the availability of cytokines, chemokines and growth factors [29][30][31]. Indeed, by expressing collagens and fibronectin essential for assembling conduits, FDC may help to regulate the transport of low-molecular-weight proteins [32].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][15][16][17] The molecular bidirectional crosstalk with stromal cells appears to support AML blast proliferation, [3][4][5][6][7][8][9]16,20,22 and our own prior studies demonstrated that both fibroblast cell lines HFL1 and Hs27, the osteoblastic sarcoma cell lines Cal72 and SJSA-1 and normal osteoblasts 33,34 can increase AML blast proliferation as well as release of proangiogenic IL-8 by native human AML cells. Fibroblasts also have an additional antiapoptotic effect, 22 and this effect is observed both with Hs27 and HFL1 fibroblasts (Ryningen, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,14 -16 Thirdly, stromal cells produce extracellular matrix, e.g., different collagens, proteoglycans (e.g., chondroitin sulfate, heparan sulfate, dermatan sulfate), hyaluronan and glycoproteins like fibronectin, laminin and thrombospondin. 5,10,17 One function of these molecules is to bind growth factors and thereby create a local extracellular reservoir. 17 The stromal cells together with their matrix components thereby constitute an interacting network with AML cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation